Human gut microbiota: the links with dementia development. Issue 2 (19th November 2016) - Alkasir, Rashad; Li, Jing; Li, Xudong; Jin, Miao; Zhu, Baoli
Abstract: Dementia is a comprehensive category of brain diseases that is great enough to affect a person's daily functioning. The most common type of dementia is Alzheimer's disease, which makes most of cases. New researches indicate that gastrointestinal tract microbiota are directly linked to dementia pathogenesis through triggering metabolic diseases and low-grade inflammation progress. A novel strategy is proposed for the management of these disorders and as an adjuvant for psychiatric treatment of dementia and other related diseases through modulation of the microbiota (e.g. with the use of probiotics).